Association between Bullying and Both Awake and Sleep Bruxism in School Adolescents: A Cross-Sectional Study - Taísa Figueirôa; Jakelline Raposo; Laís Soares; Luíza Oliveira; Valdenice Menezes; Viviane Colares; Carolina da Franca; Fabiana Godoy (Association of Support to Oral Health Research (APESB), 2024)
Objective: To verify the association between bullying and awake and sleep bruxism in school teenagers. Material and Methods: A cross-sectional study was conducted from March to June 2018 with adolescents aged 14 to 19 of both sexes enrolled in the state school system of a city in Pernambuco. Students who participated in the stages of data collection and filled out the questions about bullying and bruxism were considered eligible. Those with disabilities or dysfunctions that made it impossible to fill out the questionnaire themselves were excluded. For data collection, an instrument with questions from the National Survey of Adolescent Health (PeNSE) and the "Research Diagnostic Criteria for Temporomandibular Dysfunction" (RDC/TMD) questionnaire was used. Results: A total of 2,500 adolescents participated in this study. The prevalence of possible awake bruxism among the adolescents was 20.6%, the prevalence of possible sleep bruxism was 21.9%, and 23% of the adolescents reported having experienced bullying. About 2 of 10 male students had possible sleep bruxism (SB), while a fourth of the female students had the condition (p=0.004; OR=1.1). As seen in the awake bruxism, feelings of sadness, school bullying, and cyberbullying had significant correlations with possible SB (p<0.001, OR=2.4; p<0.001, OR=1.9 and p=0.01, OR=1.7, respectively). Conclusion: The association between possible awake and sleep bruxism and bullying in school adolescents was verified, regardless of sex, age, income, and mother's education.